Religious Pluralism, yet a Homogenous Stance on Interest Rate: The Case of Judaism, Christianity, and Islam - Ahmed S. Abou-Zaid; Tesa Leonce (Contemporary Economics)
Despite the conventional consensus that interest rates are efficient mechanism of allocating loanable funds and the most influential monetary policy instrument in modern economies, the three major monotheistic religions, Judaism, Christianity, and Islam, prohibit the use of interest and consider charging interest as an act of exploitation and extortion. Several passages and verses in the Torah, the Bible, and the Quran make their position on interest clear and definitive, from the Bible’s dictum, “Do not charge your brother interest” to the Quran’s exhortation “give up what remains of your demand for usury.” This paper reviews those passages and verses, provides different scholars’ perspectives on these verses, and relates them to the current financial system. The paper also presents several recent events that support the religious position by showing the negative impact of interest on countries, societies, and individuals. These events have, in fact, inspired many economists and financial institutions to seek alternatives to the current system.